Multi-Tiered Intensive Supervision: A Culturally-Informed Method of Clinical Supervision - Angie D. Cartwright; Chandra D. Carey; Huan Chen; Dominique Hammonds; Ana G. Reyes; Mickey E. White (Teaching and Supervision in Counseling, 2021)
In this exploratory phenomenological study, the authors researched the experiences of doctoral level supervisors (N=5) who piloted a new supervision approach, Multi-Tiered Intensive Supervision (MTIS). MTIS is a 13-week supervision intervention that involves hierarchical supervisory experiences which includes clinical supervision with three different professionals. This approach applies an anti-racist framework and merges the components of traditional supervision models which allows concepts such as knowledge development of multicultural counseling theory, conceptualization of the intersectionality of cultural identities and enhanced personal self-awareness across each layer of supervision. Five themes were identified: (a) recognition of power, privilege, and oppression; (b) personal impact; (c) deficits in current supervision training and models; (d) supervisory skill development; and (e) impact of MTIS. Implications and recommendations for supervisors, counselor education programs, and researchers are provided.
Keywords: Supervision; supervision models; multicultural